Morphometric Analysis of Hip Bones for Gender Identification in Unexpected Death Cases in Kabul, Afghanistan - Ahmad, Bashir Wafaa (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Unexpected deaths in Kabul Afghanistan often involve victims who cannot be identified due to facial disfigurement or missing identity documents. Gender identification is an important step in the forensic identification process, especially in cultural and religious contexts that have strict norms regarding gender. Pelvic bone morphometric analysis offers an accurate and non-invasive method for gender identification. This study aims to evaluate the effectiveness of hip bone morphometric analysis in identifying gender in cases of unexpected death in Kabul, Afghanistan. Methods: The samples consisted of 100 human pelvises, 50 of each gender, collected from skeletal remains at Kabul hospitals and burial grounds. Pelvic dimensions were measured using calibration techniques and statistical analysis was performed to identify significant morphometric differences between the gender. Results: Morphometric analysis showed significant differences in several pelvic dimensions between men and women. The most informative dimensions for gender identification are pelvic width, pelvic height, and superior diameter of the acetabulum. The prediction model developed using these dimensions achieved a gender identification accuracy of 94%. Conclusion: Pelvic bone morphometric analysis can be a valuable tool for forensic identification in cases of unexpected deaths in Kabul Afghanistan. This method offers high accuracy, is non-invasive and easy to apply, and can help in the process of identifying victims and resolving legal cases.